Upaya Diplomasi Publik Pemerintah Indonesia Dalam Meningkatkan Kunjungan Wisatawan Asal Jepang Pada Tahun2019 - Mabruri, Aditya Prima; Sushanti, Sukma; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This study aims to describe the public diplomacy efforts carried out by the Indonesian government in increasing tourist visits from Japan in 2019 using qualitative methods. The decline in Japanese tourist visits in 2018 has become one of the main focuses of the Indonesian government, especially the long history of diplomatic relations between the two countries, the large expenditure of Japanese tourists is the reason for the Ministry of Tourism to continue to increase Japanese tourist visits. This study uses the concepts of public diplomacy and nation branding to explain programs related to the Indonesian government's efforts to promote Indonesian tourism to Japanese tourists. The use of public diplomacy is considered in accordance with the promotion of Wonderful Indonesia which is Indonesia's nation branding. This research then gets answers about several selected programs carried out by the Indonesian government to achieve its goal of increasing Japanese tourist visits. However, at the end there is a conclusion that the target of increasing Japanese tourist visits in 2019 has not been achieved. Keywords : Indonesia, Japanese Tourist, Public Diplomacy, Tourism